2021
DOI: 10.1093/cercor/bhab218
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in the Dorso-Central Division of Zebrafish Pallium Respond to Change in Visual Numerosity

Abstract: We found a region of the zebrafish pallium that shows selective activation upon change in the numerosity of visual stimuli. Zebrafish were habituated to sets of small dots that changed in individual size, position, and density, while maintaining their numerousness and overall surface. During dishabituation tests, zebrafish faced a change in number (with the same overall surface), in shape (with the same overall surface and number), or in size (with the same shape and number) of the dots, whereas, in a control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…The caudal region of the central part of area dorsalis telencephali (Dc) responds to change in numerosity of a visual Stimulus [138] Numerosity-based categorization of a visual Stimulus and involvement of Dc in approach/avoidance behaviors Habituation/dishabituation experiments associated with measurements of early gene (IEGs) expression were performed on adult zebrafish by Messina et al [137]. Animals were first habituated to a set of stimuli (small dots) and then faced (dishabituation) to a similar stimulus with a change in size (threefold increased or decreased).…”
Section: Adultmentioning
confidence: 99%
See 3 more Smart Citations
“…The caudal region of the central part of area dorsalis telencephali (Dc) responds to change in numerosity of a visual Stimulus [138] Numerosity-based categorization of a visual Stimulus and involvement of Dc in approach/avoidance behaviors Habituation/dishabituation experiments associated with measurements of early gene (IEGs) expression were performed on adult zebrafish by Messina et al [137]. Animals were first habituated to a set of stimuli (small dots) and then faced (dishabituation) to a similar stimulus with a change in size (threefold increased or decreased).…”
Section: Adultmentioning
confidence: 99%
“…What are the advantages that an in-depth knowledge of a capacity for quantity discrimination in zebrafish could bring? Combining a spontaneous habituation/dishabituation paradigm with molecular biology techniques, we explored the major brain regions involved in numerosity discrimination in adult zebrafish [137,138]. Briefly, adult zebrafish were habituated to artificial stimuli (three or nine small red dots that changed in individual size, position and density while maintaining their numerousness and overall surface from trial to trial).…”
Section: Implications Of Neurobiological Research Of Number Cognition In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the neural basis of number representation revealed selectivity of response of neurons in some areas of the brain such as the parietal and prefrontal cortex in humans [37,38] and in monkeys [39,40], the nidopallium caudolaterale in crows [15,41] and the most caudal dorsal-central part of the pallium in zebrafish [42,43], suggesting that common selective pressures led to convergent evolution of numerical representation in different species [44,45].…”
Section: Numerical Discrimination Seems To Be Supported By An "Approximate Numbermentioning
confidence: 99%